2016
DOI: 10.1155/2016/9242319
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diet Supplementation with n-6/n-3 Essential Fatty Acids in a 1.2 : 1.0 Ratio Attenuates Metabolic Dysfunction in MSG-Induced Obese Mice

Abstract: Essential polyunsaturated fatty acids (PUFAs) prevent cardiometabolic diseases. We aimed to study whether a diet supplemented with a mixture of n-6/n-3 PUFAs, during perinatal life, attenuates outcomes of long-term metabolic dysfunction in prediabetic and obese mice. Seventy-day-old virgin female mice were mated. From the conception day, dams were fed a diet supplemented with sunflower oil and flaxseed powder (containing an n-6/n-3 PUFAs ratio of 1.2 : 1.0) throughout pregnancy and lactation, while control dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Adiposity can also be associated with insulin concentration [12] and previous report that ALA prevents high insulin release [13]. Martin, et al [14] observed that ALA during pregnancy and lactation improving glucose tolerance, insulin sensitivity and reducing the fat mass stores in induced obese mice. However, Heskey, et al [15] related that higher adipose tissue ALA was inversely associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Adiposity can also be associated with insulin concentration [12] and previous report that ALA prevents high insulin release [13]. Martin, et al [14] observed that ALA during pregnancy and lactation improving glucose tolerance, insulin sensitivity and reducing the fat mass stores in induced obese mice. However, Heskey, et al [15] related that higher adipose tissue ALA was inversely associated with insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To induce obesity, new-born Swiss mice underwent subcutaneous injection of MSG (Sigma, St. Louis, USA; 4 mg/g body weight) from day 1 to day 6 after control mice received an equimolar solution of saline injected in animals of the obese group 24 . The mice were separated after weaning by sex and weighed every 10 days; only male mice were used.…”
Section: Methodsmentioning
confidence: 99%
“…The flavor enhancer monosodium glutamate (MSG) is well-known for its action to induce obesity and metabolic abnormalities in mice by its toxic effects on the arcuate nucleus, a critical hypothalamic nucleus involved in body mass and energy metabolism regulation (121)(122)(123)(124).…”
Section: Food Additivesmentioning
confidence: 99%
“…In addition to surfactants and emulsifiers, the widely used food preservative 3-tert-butyl-4-hydroxyanisole (3-BHA) induced adipocyte differentiation in 3T3-L1 preadipocytes ( 118 ); moreover, 3-BHA exposure increased adiposity and lipid plasma levels in exposed mice ( 119 ). The flavor enhancer monosodium glutamate (MSG) is well-known for its action to induce obesity and metabolic abnormalities in mice by its toxic effects on the arcuate nucleus, a critical hypothalamic nucleus involved in body mass and energy metabolism regulation ( 120 , 121 , 122 , 123 ). Notably, the central effects of MSG to promote obesity depend upon its entrance in the brain, which, in turn, is observed when it is administered centrally to adult mice or peripherally to neonate mice since the latter exhibit an immature blood-brain barrier allowing the passage of MSG ( 123 , 124 ).…”
Section: Obesogens Old and Newmentioning
confidence: 99%